Evaluasi Usability Situs Web Sistem Informasi Aplikasi Pelayanan Elektronik (SIAPEL) Malang Kota menggunakan Metode Cognitive Walkthrough - Ade Gunawan; Intan Sartika Eris Maghfiroh; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Department of Population and Civil Registration (Dukcapil) of Malang City is responsible for managing the population administration of the people of Malang City. This management is supported by an information system that capable of serving population administration activities through the Sistem Informasi Aplikasi Pelayanan Elektronik (SIAPEL) Malang Kota website. Based on an interview with the Dukcapil of Malang City, the SIAPEL Malang Kota website has only been used by a small number of people in Malang City and its usability aspect has never been evaluated. Therefore, it is necessary to evaluate to see the level of usability and quality of the services provided. The purpose of this study was to see the level of usability on the SIAPEL Malang City website and provide recommendations for design improvements from the usability problems found. Evaluation using the Cognitive walkthrough method involves six evaluators. Each evaluator works on 11 task scenarios, then answers four thought provoking questions (TPQ). The results of the evaluation found 25 usability problems, then analyzed so that they became 21 unique usability problems. The most usability problems found by evaluator 5 were eight problems, most were found in task scenario 8 with seven problems, and most related to TPQ2 questions with 13 problems. Usability issues are discussed for improvement suggestions. These suggestions become the main source in the preparation of recommendations for improvement. The improvement design refers to the HHS Guidelines. Design improvements on the SIAPEL Malang Kota website resulted in design improvements on nine pages with a total of 11 designs.